Testing React.js applications with Jest : a complete introduction to fast, easy testing - Sayfan, Gigi (Apress, 2019)
"Learn how to use Jest by viewing easy-to-follow screencasts accompanied by clear instructions. In this complete video introduction to Jest, the testing framework from Facebook, you'll discover how Jest can test any JavaScript application, and that it is widely used to test React.js applications. Testing React.js Applications with Jest will lay out the entire process, allowing you to see Jest in action with your own eyes. You'll see that comprehensive testing of JavaScript-based web applications is a significant task, and many of the solutions that have emerged over the years have been cumbersome and involved integrating many different tools. With the help of this video you'll replace these multiple tools and create a fast, comprehensive service that supports advanced features such as snapshots. Along the way you'll learn how to build Jest into applications using create-react-app. This video course will cover Jest performance, ease of use and configuration, mocking and advanced features - it is a comprehensive guide to the framework that will make testing React.js applications a breeze."--Resource description page